Money and Modernity : Pound, Williams, and the Spirit of Jefferson. - Marsh, Alec (University of Alabama Press, 2011)
Marsh locates Pound and Williams firmly in the Jeffersonian tradition and examines their epic poems as manifestations of a Jeffersonian ideology in modernist terms. The modernist poets William Carlos Williams and Ezra Pound were latter-day Jeffersonians whose politics and poetry were strongly marked by the populism of the late 19th century. They were sharply aware of the social contradictions of modernization and were committed to a highly politicized, often polemical poetry that criticized finance capitalism and its institutions--notably banks--in the strongest terms. Providing a his.